Constraining the age of superimposed glacial records in mountain environments with multiple dating methods (Cantabrian Mountains, Iberian Peninsula). (1st September 2018) - Rodríguez-Rodríguez, Laura; Domínguez-Cuesta, María José; Rinterknecht, Vincent; Jiménez-Sánchez, Montserrat; González-Lemos, Saúl; Léanni, Laëtitia; Sanjurjo, Jorge; Ballesteros, Daniel; Valenzuela, Pablo; Llana-Fúnez, Sergio
Abstract: Numerous cases of timing differences between glacier advances recorded in mountain environments have been documented over the last decade, usually suggesting potential age conflicts between the different dating techniques. The frequent use of a single technique to date numerically a given glacial sequence makes it difficult to address to what extent age differences can be an artifact related to biased numerical age results or a paleoclimate signature. Here we present a new set of 43 numerical ages based on three dating techniques — 10 Be surface exposure dating; radiocarbon; and optically stimulated luminescence— that complement the chronology of Pleistocene glacial advances in the Porma valley, in the central Cantabrian Mountains of Spain. Results compliment previous chronologies in the area, supporting an important glacial advance during Marine Isotope Stage 3 (Stage IIa: ∼56 ka) that culminated with the Last Glacial Maximum advance (Stage IIb: ∼33–24 ka) of MIS 2 in response to increased rainfall and solar insolation minima. Glacier fronts reached elevations as low as 1130 m a.s.l. possibly without overriding evidence related to the previous Pleistocene glacial maximum extent. Glacier recession in the Cantabrian Mountains started at 21–20 ka ago, after the global LGM. We suggest that the recession was initiated by increased insolation followed by hyper-cool and dry conditions during Heinrich Stadial 1 in response to meltwater discharges in the North Atlantic. Highlights: Multi-dating approaches are the most adequate to built robust glacial chronologies. 10 Be CRE, OSL and 14 C results are cross-compared in the Porma valley. Glaciers advanced in MIS 2 (33–24 ka) inside the limits of previous glaciations. Recession began during the LGM (23–19 ka) due to increased solar insolation.